The Effect of Admixture on Mortar in 3D Printing Technology - Setioningsih, Retnowati (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2021)
Abstract. Mortar is made from a mixture of sand, cement and water. In order to obtain good extrude results for the application of 3D printing technology, in this research, mortar was added with admixture materials. There are two types of admixture in mortar, those are chemical admixture and pozzolan admixture. The highest compressive strength was obtained from Mortar+Pozzolan of 37.5 MPa, while the best flowtable and the best results from the extrude of 3D printing machine was Mortar+Chemical+Pozzolan. Keywords: mortar, extrude, chemical, pozzolan